Analyze On Variation Composition of Composite Polymer Foam Polyurethane Reinforced by Bagasse Waste Due to Static Compressive Loading - Aidi Sutikno; Zainal Arif; Taufan Arif Adlie (Fakultas Teknik Universitas Samudra, 2022)
At this time, the discovery in the field of composites continues to grow. Using foamed polymer composites reinforced with natural fibers continues to be researched and developed to obtain alternative materials to replace metals. Composite materials have unique characteristics and are lighter in weight. Natural fibers from bagasse fiber can function as reinforcement in polymer composites. This study aimed to obtain the effect of variations in bagasse fiber on composite polymer foam materials due to compressive strength loads. This polymer composite material was made by varying bagasse fiber with a mesh fiber size of 300, 400, and 500. Three variations of the constituent materials were measured based on the density ratio of the materials. The constituent materials consist of resin, polyurethane, and fiber, respectively are: label A = (85%, 15%, 0%); label B = (84%, 15%, 1%); Label C = (83%,15%, 2%); and label D = (82%, 15%, 3%). Specimens, for each composition, are three specimens. The technique for making specimens uses the method of pouring into molds concerning ASTM D-638. The testing machine for compressive strength of this polymer composite material using the Tensilon RTF-1350 tool. From the data obtained from the results of the maximum compressive strength test occurs in the fiber size of the specimen labeled D (500 Mesh) with a compressive stress of 5.674 MPa and a strain of 0.186 mm/mm. From these data, it can be concluded that the smaller the size of the bagasse fiber, the better the tensile strength of the polymer foam composite material.